Análise do pólen nas provisões lavais de Centris (Heterocentris) Analis Fabricius, 1804 (Apidae, Centridini) em agroecossistema com cultivo de aceroleira (Malpighia Emarginata DC) no semiárido baiano - Santos, Ricardo Moreira (2011)
The knowledge about the sources of floral resources explored by bees of genus Centris Fabricius has essential importance for delimitation of strategies aiming to conservation and management of these insects for crop pollination in agroecosystems. The aim of this work was to analyze the pollen contained in the larval provisions of Centris (Heterocentris) analis Fabricius, 1804 in an agroecosystem with West Indian cherry crop (Malpighia emarginata DC, Malpighiaceae) on a family farming system in the region of Feira the Santana, Bahia, Brazil. The pollen present in provisions of 55 brood cells from 32 nests founded by females of C. analis in trap nests was sampled, between the months of november 2008 and april 2009, and between September 2009 and august 2010. The samples were treated by the acetolysis method. It was countered 63.005 pollen grains, from which 36 pollen types related to 20 plant families were identified. The analysis of pollen contained in larval provisions of C. analis indicated that the pollen types related to Malpighiaceae family, bodily, presented the highest frequence of relative occurrence between the plant families related (77,27% from the sum of pollen grains countered), followed by the pollen types related to Leguminosae (14,30% from the sum of pollen types) and Solanaceae (3,27% from the sum of the pollen types). The frequence of ocurrence analysis indicated the type Malpighia emarginata as the most representative among the pollen types found, corresponding to 75,58% from the sum of pollen types countered, followed by Cajanus cajan (10,54%), Chamaecrista type 01 (3,28%) and Solanum paniculatum (2,98%), being that the plant species related to these pollen types were considered the most important pollen sources for the females of C. analis in the study area. The pollen spectrum registered in the nests also indicated the exploration of several nectar sources by the females of C. analis along the sampling period, from which we can cite the plant species related to pollen types Anacardium occidentale, Bowdichia virgilioides, Melochia/Walteria type 01 and Passiflora sp. as the most important sources of this resource for the C. analis larvae in this area. The values of trophic niche width (H') and equitability (J') for the use of sources of floral resources were variable along the sampling period, being the highest values observed in the months with less frequence of occurrence of pollen of M. emarginata in the provisions of nests of C. analis, coupled with a greater frequence of occurrence of pollen of alternative sources of floral resources for these bees in the studied area. Based on the data from the pollen samples analysed, M. emarginata can be considered the main pollen and floral oil source for this bee specie in the region of Feira de Santana, BA. At the same time, the ocurrence of pollen types related to several ruderal and cultivated species points to the importance of these plants as alternative sources of floral resources for the natural populations of C. analis in the studied area.